2018
DOI: 10.1609/aaai.v32i1.11468
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Democracy: An Algorithmic Perspective

Abstract: We study liquid democracy, a collective decision making paradigm that allows voters to transitively delegate their votes, through an algorithmic lens. In our model, there are two alternatives, one correct and one incorrect, and we are interested in the probability that the majority opinion is correct. Our main question is whether there exist delegation mechanisms that are guaranteed to outperform direct voting, in the sense of being always at least as likely, and sometimes more likely, to make a correct decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…They find that adding a cost polynomial in the number of representatives and a benefit of choosing the correct outcome polynomial in the number of voters decreases the optimal congress size to O(log n). Finally, this work supports, to some extent, propositions to constitute assemblies of citizens under fluid democracy (Miller 1969;Blum and Zuber 2016;Green-Armytage 2015;Christoff and Grossi 2017;Kahng, Mackenzie, and Procaccia 2021;Gölz et al 2018;Halpern et al 2021) that would vote on behalf of the entire population. Indeed, fluid democracy could yield very large citizen assemblies deemed desirable by our findings.…”
Section: Discussionsupporting
confidence: 77%
“…They find that adding a cost polynomial in the number of representatives and a benefit of choosing the correct outcome polynomial in the number of voters decreases the optimal congress size to O(log n). Finally, this work supports, to some extent, propositions to constitute assemblies of citizens under fluid democracy (Miller 1969;Blum and Zuber 2016;Green-Armytage 2015;Christoff and Grossi 2017;Kahng, Mackenzie, and Procaccia 2021;Gölz et al 2018;Halpern et al 2021) that would vote on behalf of the entire population. Indeed, fluid democracy could yield very large citizen assemblies deemed desirable by our findings.…”
Section: Discussionsupporting
confidence: 77%
“…Their objective is to assign delegations in such a way as to minimize the maximal voting weight of agents. Kahng, Mackenzie, and Procaccia (2021) consider an epistemic setting in which each agent has a competence level (i.e., probability of making the "correct" voting decision) and an approved subset of other agents. They are interested in (possibly randomized) delegation mechanisms that increase the likelihood of a correct decision compared to direct voting.…”
Section: Related Workmentioning
confidence: 99%
“…Several works have argued that these super-voters are or could be detrimental. Within the theoretical model of voter competence in Kahng et al [19], super-voters can make liquid democracy less likely than direct democracy to choose the correct outcome in the worst-case due to a wisdom of the crowd effect. On the practical side, Kling et al [20] observed that the presence of super-voters may have discouraged other voters from participating, but ultimately concluded that, "While we find that the theoretical and potential power of super-voters is indeed high, we also observe that they stabilise the voting system and prevent stagnation while they use their power wisely.…”
Section: 24mentioning
confidence: 99%
“…Originally championed by Charles Dodgson (AKA Lewis Carroll) in 1884 [8,25], liquid democracy is an old idea that has attracted renewed interest from both computer science [4,5,7,14,19,21,26] and political philosophy [3] perspectives. The basic concept is simple: it is a voting system in which each agent can choose to either vote directly or delegate their vote(s) to another agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation